2021
DOI: 10.2147/cmar.s290327
|View full text |Cite
|
Sign up to set email alerts
|

Multiphase Contrast-Enhanced CT-Based Machine Learning Models to Predict the Fuhrman Nuclear Grade of Clear Cell Renal Cell Carcinoma

Abstract: Objective To investigate the predictive performance of different machine learning models for the discrimination of low and high nuclear grade clear cell renal cell carcinoma (ccRCC) by using multiphase computed tomography (CT)-based radiomic features. Materials and Methods A total of 137 consecutive patients with pathologically proven ccRCC (including 96 low-grade [grade 1 or 2] and 41 high-grade [grade 3 or 4] ccRCC) from January 2011 to January 2019 were enrolled in t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
11
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(14 citation statements)
references
References 32 publications
1
11
0
2
Order By: Relevance
“…Most previous studies constructed ML models only based on CT radiomics features, which ignored the importance of traditional clinical and radiological information [ 26 , 41 , 44 ]. In our study, some parameters with clinical and radiological information that have the potential to be risk factors in the WHO/ISUP nuclear grade of CCRCC determined by multivariate regression model were fed into ML model, and the radiomics features combined with the clinicoradiological characteristics showed a better performance for the discrimination of CCRCC grades.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Most previous studies constructed ML models only based on CT radiomics features, which ignored the importance of traditional clinical and radiological information [ 26 , 41 , 44 ]. In our study, some parameters with clinical and radiological information that have the potential to be risk factors in the WHO/ISUP nuclear grade of CCRCC determined by multivariate regression model were fed into ML model, and the radiomics features combined with the clinicoradiological characteristics showed a better performance for the discrimination of CCRCC grades.…”
Section: Discussionmentioning
confidence: 99%
“…All patients were injected with nonionic intravenous contrast agent, via the antecubital vein with mechanical power injector, according to their weight (1 mL/kg body weight, with a maximum of 150 mL). Phase and delay time were as follows: Phase 1, unenhanced; Phase 2, postcontrast corticomedullary phase (CMP): 25–28 s after contrast agent was administrated; Phase 3, postcontrast nephrographic phase (NP): 65–70 s after contrast agent was administrated; and Phase 4, postcontrast excretory phase [ 26 ].…”
Section: Methodsmentioning
confidence: 99%
“…Several studies have demonstrated that machine learning (ML)-based CT radiomics models can distinguish Fuhrman grade or WHO/ISUP grade of CCRCC (17,19,(28)(29)(30). However, most of these studies built ML models based on radiomics features only, neglecting the importance of clinical and radiological characteristics (17,19). The radiomics-derived data are not a panacea for computerized clinical decision- (35).…”
Section: Discussionmentioning
confidence: 99%
“…Pre-contrast CT of the abdomen was first acquired, followed by two post-contrast CT scans obtained in corticomedullary phase (CMP, 25-28 s after contrast agent was administrated) and nephrographic phase (NP, 65-70 s after contrast agent was administrated). Finally, excretory phase was acquired (EP, 6-8 min after contrast agent was administrated) (17)(18)(19).…”
Section: Ct Imaging Parametersmentioning
confidence: 99%
“…Preoperative noninvasive prediction of ccRCC is conducive to delivering an individualized treatment. Previous studies ( 12 , 13 ), using radiation characteristics based on multiphase CT, investigated the predictive performance of different machine learning models for discriminating ccRCC. Beyond that ( 14 17 ), have shown that convolutional neural networks based on single or multiphase CT images are beneficial for evaluating ccRCC grading.…”
Section: Introductionmentioning
confidence: 99%